Development Of Samia Silkworms, Cassava Leaves And Sissy Plants With Medicinal Properties In Yard Intensification With Simple Agroforestry Patterns For The Younger Generation In The Widodomartani Community, Ngemplak, Sleman, Special Region of Yogyakarta - Prijono, Agus; ., Rawana; Woesono, Hastanto Bowo; Nugroho, Yunianto Hargo (Fakultas Teknologi dan Industri Pangan Unisri Surakarta, 2024)
The Widodomartani community has practiced land management in their yard with simple agroforestry as a form of intensification. For the younger generation to understand the practice of agroforestry from an early age, it is necessary to introduce it so that they are motivated to practice it as part of the family income. There are 4 forms of agroforestry, namely trees planted regularly with non-tree plants, there are 2 compositions, namely sengon trees with kimpul, Japanese papaya, sissy. Trees were planted around the land and non-tree trees, such as mahogany, cassava, sweet potato, chili, papaya, ginger, turmeric, galangal, and sissy were planted inside. Mixed trees with 2 trees, namely the composition of mahogany trees, coffee, and mahogany trees, wadang, melinjo, coffee, sissy. Mixed trees next to it are land planted with non-tree 1 composition of mahogany, melinjo, ketapang, johar and the land next to it is banana, papaya, moringa, ginger, chili, spinach, tomato, eggplant, sissy. 2 plants are trying to be more popularized, namely the Sissy plant and Cassava or Cassava. The sissy plant is popularized because it is easy to grow in various conditions, can help treat intestinal and digestive disorders, and is easy to consume like spinach. Cassava or cassava plants for added value, one of which is used to develop Samia silkworm silk.